Open femoral neck fracture of 14 years old boy treated by emergency internal fixation with additional osteomuscular pedicle graft: case report - Kumara, Hendra C.; Nasution, Ariya M.; Jiwandono, Bayu S.; Satriadi, Anung B.; Utomo, Pamudji (International Journal of Research in Orthopaedics, 2020)
The incidence of femoral neck fractures in pediatric patients is rare, including <1% in all cases of fractures in children. The mechanism of injury is a high-energy injury that can cause a fracture in the femoral neck, open fracture cases are rare. Avascular necrosis is the most common complication. We report a fourteen year old boy who was in a road-traffic accident and had a Gustillo Anderson grade IIIA open femoral neck fracture. On the X-ray findings, we classified the type of fracture into Delbet type II. We decided to do the debridement and ORIF accompanied by an osteomuscular pedicle graft using a quadratus femoris muscle tendon fixed with 3 interfragmentary screws. Short-term evaluation shows a clinical union picture and is still well reduced without any signs of infection. Long-term evaluation of the bone healing process is needed and recognizes complications in the form of avascular necrosis of the femoral head.